Data Communications and Computer Networks: Research and Impact - Sinek Mehuli Br Perangin-angin (LPPM STIKOM Tunas Bangsa, 2024)
Science and technology have brought society to an advanced level. The use of human labor, which is becoming increasingly scarce, often results in people losing their jobs because their tasks have been replaced by equipment or machines. As a means of providing information and communication, computers can be used as a means of the Internet. Through the Internet, people can search for various information and communicate. Obtaining information for personal life, such as information about health, hobbies, recreation, and spirituality, is the role that this application of information technology can play. In addition to the benefits, it turns out that information and communication technology devices also have negative effects on their users. As a result of inappropriate or irresponsible use by users, these negative effects occur. Some of these negative effects are 1). Kids spend more time watching TV than doing other things (such as studying and playing sports), 2). Children lose the ability to mingle with society and tend to be comfortable with online life, 3) Copyright infringement, 4). Cybercrime, 5). Spread of computer viruses, and 6). Pornography, gambling, fraud, violence. The ways to overcome these negative effects are: 1). Build relationships with people you already know, 2). Find a positive community that often meets in the real world, 3). The need for law enforcement, which involves the establishment of Internet police, 4). Avoid the use of cell phones with sophisticated features by minors and supervise the use of cell phones, 5). Reading more books that are educational and faith-based as well as computer applications that are educational in nature, and 6). The need for time management in front of the computer or television.